Upaya Meningkatkan Hasil Belajar IPS Melalui Media Permainan Ular Tangga pada Peserta Didik Kelas VI SD Negeri 104/IX Kedemangan Kabupaten Muaro Jambi - Jamalia, Jamalia (UNIB Press, 2018)
The purpose of this research is to improve results learning subjects IPS through snake ladder media on grade 6 students SD No 104 / IX Kedemangan Muaro Jambi District Academic Year 2012/2013. The low learning interest of students in following the subjects of Social Sciences (IPS) which causes lowlearning outcomes of students is a major element of this research. The form of research is action research which is implemented in three cycles/ series. each cycle/ series consists of four stages namely, planning, action, observation, and reflection. There were 27 subjects, consisting of 11 males and 16 females. The method used as the main method is observation and test. The results showed that through the game media snake ladder the increased learning outcomes of IPS students, in the pre-action of the learners overall learning outcomes show percentage of 7.40% of students learn complete, after the first cycle/ series of learning results have increased in the amount of 40.74%. However the school established KKM 60 with percentage 100% complete, the action continued in II cycle/series and then result increased by 70.37%. and then the action is continued in III cycle/series with result score of 100% complete. it can be concluded that through the game media snake ladder can improve learning outcomes of IPS in grade 6 students SD 104 / IX Kedemangan muaro jambi district academic year 2012/2013.